Doing developmental research a practical guide - Striano, Tricia (New York, NY The Guilford Press, 2016)
"Addressing practical issues rarely covered in methods texts, this user-friendly, jargon-free book helps students and beginning researchers plan infant and child development studies and get them done. The author provides step-by-step guidance for getting involved in a developmental laboratory and crafting effective research questions and proposals. Tips on recruiting study participants cover access issues--such as how to overcome language and cultural barriers--and include helpful sample scripts. The book offers time management strategies, pointers for organizing and communicating data, and a road map of the journal publication process, complete with an annotated sample article. Numerous concrete examples, checklists, worksheets, and exercises are featured. Reproducible forms can be downloaded and printed in a convenient 8 1/2" x 11" size. Pedagogical Features: *Chapter subheadings written as questions to help students quickly find the answers they need. *Boxed key tips and checklists for managing each phase of a study. *Exercises that build core research skills. *Annotated sample journal article with commentary on the writing and publication process"--Provided by publisher.
"Subject Areas/Keywords: child development, children, developmental psychology, developmental research methods, developmental science, early childhood, infancy research, infants, parents, preschoolers, research laboratory, research studies DESCRIPTION Addressing practical issues rarely covered in methods texts, this user friendly, jargon free book helps students and beginning researchers plan infant and child development studies and get them done. The author provides step by step guidance for getting involved in a developmental laboratory and crafting effective research questions and proposals. Tips on recruiting study participants cover access issues--such as how to overcome language and cultural barriers--and include helpful sample scripts. The book offers time management strategies, pointers for organizing and communicating data, and a road map of the journal publication process, complete with an annotated sample article. Numerous concrete examples, checklists, worksheets, and exercises are featured. Reproducible forms can be downloaded and printed in a convenient 8 1/2" x 11" size"--Provided by publisher.
1. Selecting a Laboratory -- 2. Your First Days and Weeks in the Laboratory -- 3. Managing your Time -- 4. Developing Your Ideas and Immersing Yourself in the Culture of Research -- 5. Developing Your Research Question and Proposal -- 6. Recruitment and Access -- 7. Organizing and Planning Your Research -- 8. Strategies for Using Statistics -- 9. Writing Up Your Research -- 10. Selecting a Journal and Establishing Authorship -- 11. Communicating Your Research.
Includes bibliographical references and index.
Keywords: Developmental psychology -- Research -- Methodology; Child development -- Research -- Methodology; Report writing